Sustainable Solutions to âComplex Problem-Solvingâ A Key to Effective Community and Industry Engagement and Partnerships by University Researchers - Richards, Cameron; Tanquilut, Neil (Department of Urban and Regional Planning, Diponegoro University, 2015)
Abstract Community and industry engagement by universities and academics are sometimes prone to accusations of exclusive or academic âtalk-festsâ which can reinforce rather than resolve the âbridgeable disconnectâ between the general community and particular organizations with vested interests (Grayson, 2010). Concrete modes and strategies of âlinking knowledge to actionâ are needed to build upon the participatory exchange or mediation of stakeholder perspectives and interests. This paper reports on the exploration, development and application of the kind of convergent and also interdisciplinary approach to development studies which might: (a) better link theory and practice as a basis for the elusive goal of strategic âsustainabilityâ, and (b) also encourage and optimize authentic, collaborative, and complex modes of problem-solving as a key to community and industry engagement by academic institutions and researchers. It will do so in relation to some practical case studies in such partnerships. Keywords: collaborative research and development; community-industry-university partnerships; complex problem-solving; interdisciplinary methodologies; sustainability